Cutaneous Hematolymphoid and Histiocytic Proliferations in Children. (April 2018) - Gru, Alejandro A; Dehner, Louis P
This article focuses on cutaneous hematopoietic neoplasms that are more likely to be encountered in the pediatric age-group and includes both lymphoproliferative and histiocytic disorders. The cutaneous hematologic disorders in children have a different epidemiologic profile to what is seen during adulthood. Although mycosis fungoides is the most frequent form of cutaneous lymphoma in adults, it is very rare in children. Because lymphoblastic leukemias and lymphomas are more frequent in the pediatric setting, cutaneous leukemic infiltrates are relatively common in this age-group. Similarly, histiocytic disorders are more common in children, particularly Langerhans cell histiocytosis and juvenile xanthogranuloma. Notably, the histiocytic disorders have undergone significant modifications on their nomenclature in the basis of the molecular characteristics that are present in them. A summary of the most frequent cutaneous hematopoietic disorders in children will be discussed further in this review.